2020
DOI: 10.3390/biotech9040022
|View full text |Cite
|
Sign up to set email alerts
|

RNF6 as an Oncogene and Potential Therapeutic Target—A Review

Abstract: The RNF6 gene encodes Ring Finger Protein 6 (RNF6), which functions as a ubiquitin ligase. Its functions are not entirely known, but research shows that it is involved in human cancer development. Initially, this gene was considered to be a tumor suppressor. Numerous statistical analyses on cell lines and animals indicate, however, that RNF6 functions as an oncogene, involved in signaling pathways, including SHP1/STAT3, AKT/mTOR, Wnt/β-catenin, or ERα/Bcl-xL. Due to this fact, it has become a potential prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…As a ubiqui tin ligase, RNF6 is primarily associated with polyubiquiti nation and degradation of other proteins [13,14]. So far, research on this protein has focused mainly on its role in cancer [4,[15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a ubiqui tin ligase, RNF6 is primarily associated with polyubiquiti nation and degradation of other proteins [13,14]. So far, research on this protein has focused mainly on its role in cancer [4,[15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…The RNF6 (Ring Finger Protein 6) gene, located on 13q12.13, encodes a zinc finger domain protein that acts as an E3 ubiquitin ligase. So far, abnormalities in this gene have been associated mainly with the development of tu mours [4]. The aim of the study is to draw attention to the chromosomal abnormality in a 3.5yearold girl, ascertain its possible impact on the clinical features, and consider the expression of the RNF6 gene as a possible aetiological factor of seizure disorders in children.…”
Section: Introductionmentioning
confidence: 99%
“…RNF6 is an E3 ubiquitin ligase and increasing evidence has indicated that RNF6 is involved in the development of various cancers (7,8,12,23,24). As a ubiquitin ligase, RNF6 regulates numerous cellular processes by ubiquitin-dependent degradation of target proteins (25).…”
Section: Discussionmentioning
confidence: 99%
“…expression was significantly negatively correlated to the survival rate of AML patients [41]. The downregulation of RNF6 was linked to AKT/mTOR signaling inactivation by total saponins from Paris forrestii [38].…”
Section: Parris Forrestiimentioning
confidence: 93%